1) 8 + 4 = -5 + 7
12 = 2
FALSE
2) y = -11x + 4
(0, -7): -7 = -11(0) + 4 ⇒ -7 = 0 + 4 ⇒ -7 = 4 False
(-1, -7): -7 = -11(-1) + 4 ⇒ -7 = 11 + 4 ⇒ -7 = 15 False
(1, -7): -7 = -11(1) + 4 ⇒ -7 = -11 + 4 ⇒ -7 = -7 True
(2, 26): 26 = -11(2) + 4 ⇒ 26 = -22 + 4 ⇒ 26 = -18 False
Answer: C
3) Input Output
0 0
1 3
2 6
3 9
4 12
5 15
6 18
Rule: input is being added by 1, output is 3 times x
4) c = 65h
5) 2x = -6
[tex]\frac{2x}{2} = \frac{-6}{2}[/tex]
x = -3
6) 8j - 5 + j = 67
9j - 5 = 67 added like terms (8j + j)
+5 +5
9j = 72
[tex]\frac{9j}{9} = \frac{72}{9}[/tex]
j = 8
7) y = mx + b
-b -b
y - b = mx
[tex]\frac{y - b}{x} = \frac{mx}{x}[/tex]
[tex]\frac{y - b}{x} = m[/tex]